Analysis of Ferritin Levels as a Risk Factor for Anemia in Adolescent Girls on the West Lombok Coast - Lestarini, Ima Arum; Ekawati, Ardiana; Irawati, Deasy; Wedayani, Anak Agung Ayu Niti; Putra, Hendra Susana (Jurnal Biologi Tropis, 2025)
Iron deficiency anemia (ADB) is a nutritional disorder that often occurs, especially in adolescent girls, due to increased nutrient requirements during growth and menstruation. Assessing ferritin levels is an important step in determining the status of iron stores in the body and identifying individuals at risk of iron deficiency anemia, especially in resource-constrained environments such as coastal areas. This study aims to determine the prevalence of anemia and iron deficiency in adolescent girls in the coastal areas of Lombok, Indonesia and analyze the relationship between ferritin levels as a risk factor for the incidence of iron deficiency anemia. The design of this study was a cross-sectional study conducted on 101 young women aged 15 - 19 years in the coastal areas of West Lombok. Ferritin levels were measured to determine iron deficiency status (< 15 ng/ml) and hemoglobin levels were used to determine anemia in adolescent girls (HB < 12 g/dl). The Chi-Squre and relative risk tests were used for statistical analysis of the relationship and risk between iron deficiency and the incidence of anemia. The results of the study found that the prevalence of iron deficiency was 40 (39.6%) and anemia was 21 (20.79%). Of the respondents who experienced anemia, 13 (61.9%) were iron deficiency anemia. There was a significant association between anemia and iron deficiency (p = 0.004) and an odd ratio value of 4.154 was obtained, indicating that adolescent girls with iron deficiency (low ferritin levels) had a 4.154 times greater risk of developing anemia compared to adolescent girls with normal ferritin levels.